Insecticidal activity and the mechanism of action of three phenylpropanoids isolated from the roots of Piper sarmentosum Roxb - Hematpoor, A.; Liew, S.Y.; Sofian-Azirun, Mohd; Awang, Khalijah (Nature Publishing Group, 2017)
Hexane, dichloromethane and methanol extracts of the roots of Piper sarmentosum Roxb. were screened for toxicity towards Sitophilus oryzae (L.), Rhyzopertha Dominica (F.), and Plodia interpunctella (Hübner) and the hexane extract exhibited the highest mortality percentage. Bioassay-guided fractionation of the hexane extract resulted in the isolation of asaricin 1, isoasarone 2, and trans-asarone 3. Asaricin 1 and isoasarone 2 were the most toxic compounds to Sitophilus oryzae, Rhyzopertha Dominica, and Plodia interpunctella. Sitophilus oryzae and Rhyzopertha Dominica exposed to asaricin 1 and isoasarone 2 required the lowest median lethal time. Insecticidal activity of trans-asarone 3 showed consistent toxicity throughout the 60 days towards all three insects as compared to asaricin 1 and isoasarone 2. Asaricin 1 and isoasarone 2 at different doses significantly reduced oviposition and adult emergence of the three insects in treated rice. Trans-asarone 3 had lowest toxicity with highest LC and LT values in all tested insects relative to its mild oviposition inhibition and progeny activity. Moreover, asaricin 1 and isoasarone 2 significantly inhibited acetylcholinesterase in comparison with trans-asarone 3 and the control. Acetylcholinesterase inhibition of Rhyzopertha Dominica and Plodia interpunctella by asaricin 1 and isoasarone 2 were lower than that of Sitophilus oryzae, which correlated with their higher resistance.